4(2y+4)=3(y-6)

Simple and best practice solution for 4(2y+4)=3(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2y+4)=3(y-6) equation:


Simplifying
4(2y + 4) = 3(y + -6)

Reorder the terms:
4(4 + 2y) = 3(y + -6)
(4 * 4 + 2y * 4) = 3(y + -6)
(16 + 8y) = 3(y + -6)

Reorder the terms:
16 + 8y = 3(-6 + y)
16 + 8y = (-6 * 3 + y * 3)
16 + 8y = (-18 + 3y)

Solving
16 + 8y = -18 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
16 + 8y + -3y = -18 + 3y + -3y

Combine like terms: 8y + -3y = 5y
16 + 5y = -18 + 3y + -3y

Combine like terms: 3y + -3y = 0
16 + 5y = -18 + 0
16 + 5y = -18

Add '-16' to each side of the equation.
16 + -16 + 5y = -18 + -16

Combine like terms: 16 + -16 = 0
0 + 5y = -18 + -16
5y = -18 + -16

Combine like terms: -18 + -16 = -34
5y = -34

Divide each side by '5'.
y = -6.8

Simplifying
y = -6.8

See similar equations:

| -28=4/5(d) | | 4+11x=-40 | | x+57+x+137=180 | | 6x+11y-10x-8y+9x-7y= | | 4+5(-3x+7)=-9 | | (.1-x)*(.2-x)= | | 48/(-18) | | 50-8x=-6 | | 26+(2y+1)= | | -2=8y+3(y+3) | | (7x-4)(3x+9)=0 | | (x+2)(5x+6)=0 | | -10x+10=-40 | | -5.2(4s+6)-1.7(2s-4)= | | 3(2x+15)=2x+20 | | -5-8x=5 | | 2.8x+1y=747.7 | | 2(x-4)=42 | | -100x-300=300 | | 3z+8=-2z+13 | | c(c-5)=0 | | 27=3/4(y) | | s^3+2s^2-25s=50 | | 6[5-(4x-4)]+7x=0 | | 4w+7=7w-14 | | 3x^2+26x+73=0 | | -5u-8=-2u+1 | | 91=9f+28 | | x+3(x-3)=3x+2+2x | | -3f+-11=70 | | a^2-8=2a | | 9(x-5)-4x=-5 |

Equations solver categories